Answer:
y = -3x+5 This has a negative slope
Step-by-step explanation:
The first step is to find the slope. We can use the formula
slope = (y2-y1)/(x2-x1)
= (-10--1)/(5-2)
= (-10+1)/3
= -9/3
=-3
Next we will use the point slope form of the equation of a line
y-y1 = m(x-x1)
y--1 = -3(x-2)
y+1 = -3(x-2)
Distribute the -3
y+1 = -3x -3*(-2)
y+1 = -3x+6
Subtract 1 from each side
y+1-1 = -3x+6-1
y = -3x+5
This is in the slope intercept form of the equation.
My answer differs from the options because I have a negative slope